Customized nutrition intervention and personalized counseling helps achieve nutrition targets in perioperative liver transplant patients. (February 2018) - Daphnee, D.K.; John, Sheila; Rajalakshmi, P.; Vaidya, Anil; Khakhar, Anand; Bhuvaneshwari, S.; Ramamurthy, Anand
Summary: Background and aim: Nutritional therapy is an integral part of care in all phases of liver transplantation (LTx). However, there are several factors that make it a challenge to manage malnutrition in these patients including, but not limited to, loss of appetite, dietary restrictions and dietary habits. Dietary habits are guided by personal choice, social, cultural and regional background with diversity ranging from veganism to vegetarianism with the latter predominant in Indian population. Therefore, it is difficult to improve nutritional intake of patients with standard dietary recommendations. We evaluated the effects of implementing personalized dietary counseling and a customized nutrition plan on its ability to enhance oral intake and, thereby improve nutritional status of patients with end stage liver disease (ESLD) being evaluated for LTx. We compared the outcomes with a matched group of patients who were prescribed standard dietary recommendations from a historic database. Primary outcome was measured by number of patients achieving ≥75% of recommended energy and protein requirements during hospitalization for LTx. Secondary outcomes included mean energy and protein intake, hours of ventilation, length of stay in Intensive Care Unit (ICU) and hospital, mortality and readmission rate in the acute phase (3months) after LTx. Methods: This was a prospective observational study, performed at a single LTx centre. All patients >18years who enrolled for LTx and consented for the study were included. The study was conducted after obtaining institutional ethics committee approval. A protocol based nutrition planning was implemented from April'14. According to this protocol, all patients being evaluated for LTx underwent a detailed nutritional assessment by a qualified Clinical Dietitian (CD) and regularly followed up with until LTx. Nutritional intervention, including a customized nutrition care plan and personalized dietary counseling, was provided based on the severity of malnutrition. To evaluate the efficacy of this protocol, we compared the nutritional adequacy (calorie and protein intake) of 65 consecutive patients who underwent LTx between August'14–October'15 (group 1) with a historic database of 65 patients who underwent LTx between January'13 and April'14 (group 2). Patients' demographics, disease severity score, baseline markers of nutritional status (subjective global assessment (SGA), and body mass index (BMI)), were recorded. First, assessment of individual patient's oral energy and protein intake was determined by the daily calorie count during hospitalization. Then the nutritional intervention (oral nutrition supplement (ONS)/enteral nutrition (EN)/parenteral nutrition (PN)) plan was customized according to their spontaneous oral intake. As part of the protocol, health related quality of life was also assessed using short form 8 (SF-8) in group 1. Statistical analyses using Pearson's correlation, Chi–Square test were applied with SPSS version 20.0. Results: The mean age of group 1 and 2 were 52.6 ± 9.8, 51.9 ± 10.5 (range 25–70years) with BMI of 26.8 ± 6.0, 26.5 ± 5.4 respectively. According to SGA, there was significant improvement in the nutritional status of group 1 patients compared to group 2 on admission for LTx. It was indicated that 88% of group 1 individuals in comparison to 98% in group 2 were malnourished. The calorie intake of group 1 (1740.2 ± 254.8) was significantly higher than group 2 (1568.5 ± 321.6) (p = 0.005). The marked improvement in protein intake in group 1 (63.1 ± 12.1) when compared with group 2 (53.1 ± 13.4) was statistically significant (p = 0.008). A subset analysis showed that non-vegetarians (consuming meat and dairy products) between the groups showed that group 1 had a significantly higher calorie (p = 0.004) and protein (p = 0.0001) intake compared to individuals in group 2. Following implementation of study's protocol, the goal of achieving ≥75% of the prescribed calories (p = 0.013) and protein (p = 0.0001) was significantly higher in group 1. Conclusion: When compared to the standard prescription, an individualized protocol to diagnose, stratify the severity of malnutrition early, and follow up by customized nutrition planning for patients helped to achieve nutritional targets more effectively. Inspite of patients' diversity in nutritional habits and reluctance to accept change, it is clear that a qualified and dedicated transplant nutrition team can successfully implement perioperative nutrition protocol to achieve better nutritional targets.